Analysis of Android malware detection techniques: a systematic review - Ashawa, Moses Aprofin; Morris, Sarah (Society of Digital Information and Wireless Communications, 2019)
The emergence and rapid development in complexity and popularity of Android mobile phones has created proportionate destructive effects from the world of cyber-attack. Android based device platform is experiencing great threats from different attack angles such as DoS, Botnets, phishing, social engineering, malware and others. Among these threats, malware attacks on android phones has become a daily occurrence. This is due to the fact that Android has millions of user, high computational abilities, popularity, and other essential attributes. These factors influence cybercriminals (especially malware writers) to focus on Android for financial gain, political interest, and revenge. This calls for effective techniques that could detect these malicious applications on android devices. The aim of this paper is to provide a systematic review of the malware detection techniques used for android devices. The results show that most detection techniques are not very effective to detect zero-day malware and other variants that deploy obfuscation to evade detection. The critical appraisal of the study identified some of the limitations in the detection techniques that need improvement for better detection.
Keywords: Malware; detection techniques; Android mobile device; detection rate; static detection; hybrid detection; dynamic detection; cyber security